William McKinley papers - McKinley, William, 1843-1901.
Correspondence, speeches, will, messages, scrapbooks, printed matter, and other papers pertaining primarily to McKinley's presidential administration. Subjects include Ohio state politics, presidential elections of 1896 and 1900, gold standard, McKinley tariff, progressivism, Spanish-American War, territorial expansion, and McKinley's assassination.
Includes copies of outgoing letters signed by John Addison Porter and George B. Cortelyou, presidential secretaries. Correspondents include Alvey A. Adee, R.A. Alger, John Rutter Brooke, Joseph Hodges Choate, Grover Cleveland, Henry Clark Corbin, Shelby M. Cullom, Charles Gates Dawes, William R. Day, Joseph Benson Foraker, John Fowler, Lyman J. Gage, James A. Garfield, James Albert Gary, Murat Halstead, Marcus Alonzo Hanna, John Hay, Rutherford Birchard Hayes, Garret A. Hobart, Philander C. Knox, Henry Cabot Lodge, John Davis Long, John Tyler Morgan, Henry C. Payne, Thomas Collier Platt, Theodore Roosevelt, Elihu Root, John Sherman, William H. Taft, James Wilson, Leonard Wood, and John Russell Young.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Geography and Map Division.
Library of Congress Music Division.
Library of Congress Prints and Photographs Division.
U.S. president, representative, and army officer, and governor of Ohio.
Keywords: Adee, Alvey A. -- 1842-1924 -- Correspondence; Alger, R. A. -- 1836-1907 -- Correspondence; Brooke, John Rutter, -- 1838-1926 -- Correspondence; Choate, Joseph Hodges, -- 1832-1917 -- Correspondence; Cleveland, Grover, -- 1837-1908 -- Correspondence; Corbin, Henry Clark, -- 1842-1909 -- Correspondence; Cortelyou, George B. -- 1862-1940 -- Correspondence; Cullom, Shelby M. -- 1829-1914 -- Correspondence; Dawes, Charles Gates, -- 1865-1951 -- Correspondence; Day, William R. -- 1849-1923 -- Correspondence; Foraker, Joseph Benson, -- 1846-1917 -- Correspondence; Fowler, John, -- 1858-1923 -- Correspondence; Gage, Lyman J. -- 1836-1927 -- Correspondence; Garfield, James A. -- 1831-1881 -- Correspondence; Gary, James Albert, -- 1833-1920 -- Correspondence; Halstead, Murat, -- 1829-1908 -- Correspondence; Hanna, Marcus Alonzo, -- 1837-1904 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Hayes, Rutherford Birchard, -- 1822-1893 -- Correspondence; Hobart, Garret A. -- 1844-1899 -- Correspondence; Knox, Philander C. -- 1853-1921 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Long, John Davis, -- 1838-1915 -- Correspondence; McKinley, William, -- 1843-1901 -- Assassination; Morgan, John Tyler, -- 1824-1907 -- Correspondence; Payne, Henry C. -- 1843-1904 -- Correspondence; Platt, Thomas Collier, -- 1833-1910 -- Correspondence; Porter, John Addison, -- 1856-1900 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Sherman, John, -- 1823-1900 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Wilson, James, -- 1835-1920 -- Correspondence; Wood, Leonard, -- 1860-1927 -- Correspondence; Young, John Russell, -- 1840-1899 -- Correspondence; Elections -- United States -- 1896.; Elections -- United States -- 1900.; Gold standard -- United States; McKinley tariff; Progressivism (United States politics); Spanish-American War, 1898.; Tariff -- United States; Ohio -- Politics and government -- 1865-1950.; United States -- Economic policy; United States -- Foreign relations -- 1897-1901.; United States -- Politics and government -- 1897-1901.; United States -- Territorial expansion; Governors -- Ohio; Presidents -- United States; Representatives, U.S. Congress -- Ohio